Comparison of the Use of Hypnotic in Psychiatric Patients with Insomnia at the Mental Health Centre Prolet in Skopje - Isjanovski, Viktor; Isjanovski, Igor (Scientific Foundation SPIROSKI, 2019)
Insomnia is a symptom complex that comprises difficulties falling asleep, staying asleep or non-refreshing sleep in combination with daytime dysfunction or distress. Most people experience insomnia at some time during their lives. Because of its high incidence, and also because its symptoms are usually mild and transient, the importance of insomnia is frequently underestimated. Various conditions are associated with insomnia and can contribute to its development. They can be related to neurological or psychiatric disorders, which in turn may be aggravated by a deficiency of restorative sleep and daytime fatigue.